2. Work in Progress: Dying to save the City in Athens and Boeotia: Postdoctoral research - Ioannis Mitsios (Teiresias Journal Online, 2024)
Ioannis MISIOS (National and Kapodistrian University of Athens) Dying to save the City in Athens and Boeotia. Postdoctoral research